2023
DOI: 10.1093/humrep/dead229
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for targeted, neo-evolutionary-oriented, secondary prevention of early-onset endometriosis and adenomyosis. Part I: pathogenic aspects

Paolo Vercellini,
Veronica Bandini,
Paola Viganò
et al.

Abstract: The potential for repeated ovulation and menstruation is thought to have provided a Darwinian advantage during the Palaeolithic. Reproductive conditions remained relatively stable until the pre-industrial era, characterized by late menarche, very young age at first birth, multiple pregnancies, and prolonged periods of lactational amenorrhoea. For hundreds of thousands of years, menstruators experienced few ovulatory cycles, even though they were genetically adapted to ovulate and menstruate every month. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 202 publications
(494 reference statements)
0
4
1
Order By: Relevance
“…For more than 20 years now, we have been claiming that iron plays a crucial role in endometriosis ( Van Langendonckt et al , 2002a , b ) and advocating use of iron chelators, since they were shown to prevent initiation and progression of the disease in murine models ( Defrère et al , 2011 ). Despite our findings, iron chelators were never developed in clinical research for treatment of endometriosis, but the role of highly toxic Hb by-products like iron was highlighted in two recent reviews published by Wyatt et al (2023) and Vercellini et al (2024) .…”
Section: Hemoglobin and Ironcontrasting
confidence: 67%
See 1 more Smart Citation
“…For more than 20 years now, we have been claiming that iron plays a crucial role in endometriosis ( Van Langendonckt et al , 2002a , b ) and advocating use of iron chelators, since they were shown to prevent initiation and progression of the disease in murine models ( Defrère et al , 2011 ). Despite our findings, iron chelators were never developed in clinical research for treatment of endometriosis, but the role of highly toxic Hb by-products like iron was highlighted in two recent reviews published by Wyatt et al (2023) and Vercellini et al (2024) .…”
Section: Hemoglobin and Ironcontrasting
confidence: 67%
“…Determining the pathogenesis of endometriosis remains a challenge for gynecologists, reproduction specialists, endocrinologists, and researchers alike. Multifactorial causes have been reported, including ectopic endometrial tissue, altered immunity, unbalanced cell proliferation and apoptosis, oxidative stress and reactive oxygen species (ROS), aberrant endocrine signaling, and genetic factors ( Bulun et al , 2019 ; Kapoor et al , 2021 ; Taylor et al , 2021 ; Donnez and Cacciottola, 2022 ; Vercellini et al 2024 ). However, a very comprehensive understanding is needed to detect and investigate the physiological, cytological and immunological events, as well as biochemical factors like oxidative stress and inflammation, encountered in the pelvic microenvironment of endometriosis patients.…”
mentioning
confidence: 99%
“…Certain risk factors like a larger number of ovulatory cycles (early menarche/late menopause) [13], less pregnancies (infertility, nulliparity) [14], and a shorter breastfeeding duration [15] contribute to the malignant transformation of endometriosis into ovarian cancer [16]. Generally, a hormonal imbalance with an estrogen excess and progesterone deficit promotes the development of EOAC [17].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Consequently, they concluded that the role of retrograde menstruation should not be taken for granted, as it has not been conclusively proven. This has implications when considering the pathogenesis of EOE [40]. Another important but poorly understood question is the duration of time needed from first exposure to retrograde menstruation to disease development.…”
Section: Retrograde Menstrual Bleeding In the Adult And The Neonatementioning
confidence: 99%